Lumbar Adding-on of the Thoracic Spine After Selective Fusion in Adolescent Idiopathic Scoliosis Lenke Types 1 and 2 Patients: A Critical Appraisal. Issue 3 (1st February 2021) - Tan, Jun-Hao; Hey, Hwee Weng Dennis; Wong, Gordon; Wong, Hee-Kit; Lau, Leok Lim
Abstract : Study Design: Retrospective cohort study. Objective: This study aimed to identify risk factors that predict lumbar curve adding-on in patients who had selective thoracic fusion. Summary of Background Data: Selective thoracic fusion offers deformity correction of Lenke 1 and 2 thoracic curves and maintains lumbar range of movement. However, some patients may develop postoperative lumbar adding-on. Methods: This study included patients 18 years or younger that underwent spinal instrumentation for Lenke 1 and 2 curves. Results: A total of 161 patients were included (147 females, 14 males). The mean age was 14.0 ± 2.1 years: 103 patients were Lenke 1, and 58 patients were Lenke 2 curves. Ninety-seven patients underwent posterior approach surgery, whereas 64 via anterior approach. In the posterior approach group, 79(81.4%) patients underwent selective fusion. Ten patients (6.2%) had lumbar curve adding-on, with nine females and one male. There were seven Lenke 1 and three Lenke 2 patients. All 10 patients were lumbar modifier (a), with 5 hypokyphotic patients. Selective fusion was done in nine patients. Lumbar adding-on was seen most commonly between 6 months to 1 year postoperative period (five patients). Two patients had adding-on because of incorrect distal fusion level, six were due to 1A-R curve, one due to the inadvertent fusion from the excessive long rod at the subjacent level. In multivariate analysis, hypokyphotic patients were at higher risk of lumbar adding-on (odds ratio = 9.2). Patients with Risser classification 0, 1, 2, 3 were also at higher risk of lumbar adding-on (odds ratio =6.1). Conclusion: The incidence of lumbar curve adding-on was 6.2%. Patients who were hypokyphotic and skeletally immature are nine times and six times more likely to have lumbar adding-on, respectively. This article examines adding-on in patients who had either anterior or posterior approach scoliosis surgeries, with follow-up stretching up to 10 years. This offers the rare opportunity to examine the natural history of the adding-on phenomenon. Level of Evidence: 3 Abstract : The incidence of lumbar curve adding-on was 6.2%. Lumbar adding-on was seen most commonly between 6 months to 1 year postoperative period. Patients who were hypokyphotic and skeletally immature are 9 and 6 times more likely to have lumbar adding-on, respectively. This article examines adding-on in patients with follow-up stretching up to 10 years.